Future of internet of things (IoT) in 5G wireless networks - Passi, Abhiruchi; Batra, Deepak (International Journal of Engineering and Technology, 2017)
Internet of Things or IoT has evolved and will play a major role in our lives in the near future. Though in the nascent stage, it conceptually means an interconnected network consisting of physical objects, wearables, machines, buildings, automobiles and a variety of other types of devices that contain embedded technology to communicate and sense or interact with their internal states or external environment. With the advent of next generation 5G wireless technology around 2020, a wave of globally connected digital society will come into existence. In this paper we will discuss about the benefits which will be provided to IoT with the onset of 5G wireless technology and the challenges which IoT will offer to 5G.